2014
DOI: 10.1186/1476-072x-13-49
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging community health worker system to map a mountainous rural district in low resource setting: a low-cost approach to expand use of geographic information systems for public health

Abstract: BackgroundGeographic Information Systems (GIS) have become an important tool in monitoring and improving health services, particularly at local levels. However, GIS data are often unavailable in rural settings and village-level mapping is resource-intensive. This study describes the use of community health workers’ (CHW) supervisors to map villages in a mountainous rural district of Northern Rwanda and subsequent use of these data to map village-level variability in safe water availability.MethodsWe developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…If population data cannot be obtained through outside sources, then it must be collected. While this can be a time and resource intensive process whose cost may not justify the benefits, a recent study showed that low cost collections of village locations can be done easily and rapidly [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…If population data cannot be obtained through outside sources, then it must be collected. While this can be a time and resource intensive process whose cost may not justify the benefits, a recent study showed that low cost collections of village locations can be done easily and rapidly [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…What are these articles, and in what way do they differ from those previously selected? Some are centered on data-related methodological difficulties, whether these are linked to geo-referencing or cartographic representation, for example they are about how difficult it is to have access to Gis data on a fine scale in some rural regions, and how useful it is then to rely on previously trained community health workers in order to obtain data on the repartition of safe water for people in northern Rwanda [ 37 ]. These articles also deal with the development of pertinent cartographic approaches to represent, for example, the risk linked to natural-focal diseases [ 38 ], or for better distributing healthcare resources in developing countries [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of several methods can be seen in the table 9. [11], [15], [16], [17] [10], [11], [12], [13], [14], [15], [16] [15], [16], [17], [18], [19] Accuracy After the method was chosen, the rest of our research will continue with previous research, find something that is a contribution from research comparison of several studies with research on the validation of the enumeration process in a survey can be seen in table 10. Table 10 shows comparison of several study in decision-making with GPS data to analyze human behavior.…”
Section: The Data Used In Decision-making With Gps Datamentioning
confidence: 99%